TOOL CONTROL THE CONCENTRATION OF CARBON DIOXIDE IN THE FLUE GAS BOILERS BASED ON THE OPTICAL ABSORPTION METHOD - Vasilevskyi, Oleksandr; Dudatiev, Ihor; Ovchynnykov, Kostyantyn (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2019)
The methodology for controlling the concentration of carbon dioxide in flue gases from boilers is an optical absorption method with improved metrological characteristics. Studies done in the article, provided the new, scientifically-based theoretical and practical results that are essential for improving the accuracy at the required speed process, control the carbon dioxide concentration in dual gas boilers based on the optical absorption method with compensation effect on the factors optical converter.